Book review: Hazte gurú de base de datos. SQL diseño y normalización. By L. Ponte Cordero (Publicaciones en Ciencias y Tecnología, 2018)
The work "Become a Guru of Database" presented by the author Leonardo Ponte Cordero, discusses from an ethical, managerial and even spiritual point of view technical aspects of database design and manipulation using the Structured Query Language (SQL) and SQL-based Programming Language (PL / SQL) through a database manager under LINUX environment. It is organized into five (5) broad topics ranging from the DML (Data Manipulation Language) instructions to the creation of PL/SQL Program Blocks, useful for database administration duties. It is an easy and enjoyable reading, recommended not only for undergraduate and graduate students in areas of IT, but also for professionals whose work is related to database administration.
Keywords: Database; SQL; Book; management